2014
DOI: 10.1186/1476-069x-13-46
|View full text |Cite
|
Sign up to set email alerts
|

Should oral gavage be abandoned in toxicity testing of endocrine disruptors?

Abstract: For decades, hazard assessments for environmental chemicals have used intra-gastric gavage to assess the effects of ‘oral’ exposures. It is now widely used – and in some cases required – by US federal agencies to assess potential toxicity of endocrine disrupting chemicals (EDCs). In this review we enumerate several reasons why gavage is not appropriate for the assessment of EDCs using bisphenol A (BPA) as a main example. First, whereas human dietary exposures interact with the oral mucosa, gavage exposures avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 55 publications
1
77
0
1
Order By: Relevance
“…Of importance is that the different estimates of exposure to BPA are based on the exposure models that are used (Gies et al, 2009), with one set of pharmacokinetic models being based entirely on single intra-gastric gavage exposure (LaKind et al, 2008; Volkel et al, 2002). In contrast, other exposure models assume that gavage exposure alone is inadequate to explain human serum levels of bioactive BPA (Vandenberg et al, 2010a, 2010b, 2013b, 2014b). …”
Section: Routes and Sources Of Bpa Exposure: Is Assay Contaminatiomentioning
confidence: 99%
“…Of importance is that the different estimates of exposure to BPA are based on the exposure models that are used (Gies et al, 2009), with one set of pharmacokinetic models being based entirely on single intra-gastric gavage exposure (LaKind et al, 2008; Volkel et al, 2002). In contrast, other exposure models assume that gavage exposure alone is inadequate to explain human serum levels of bioactive BPA (Vandenberg et al, 2010a, 2010b, 2013b, 2014b). …”
Section: Routes and Sources Of Bpa Exposure: Is Assay Contaminatiomentioning
confidence: 99%
“…This implies that an analysis of maternal behavior should be included, or at least considered as a possible variable, when assessing the effects of chemicals administered via maternal treatment [57]. An additional consideration regarding all the studies including maternal treatment, is that the chemical should be administered through the least invasive and stressful procedure available rather than the traditional intragastric gavage procedure used in toxicological studies conducted for regulatory purposes [58]. …”
Section: Mothersmentioning
confidence: 99%
“…With time it has been demonstrated that some of these oral manners of administration are not so suitable for the assessment of BPA. This is the case of oral gavage that does not appropriately model human dietary exposures (52). In addition, increasing evidence data have revealed that additional routes such as inhalation and contact can substantially contribute to human exposure.…”
mentioning
confidence: 99%